REPRESENTASI KONFLIK IDEOLOGI RADIKALISME DAN KONTROVERSI PADA FILM SAYAP-SAYAP PATAH: Analisis Semiotika Roland Barthes - Athaya Zhafira Jamboree (2023)
Radicalism has now become a global threat that can lead to an international crime, because it can pose a threat to world security. This condition can trigger intolerance, and at some point lead to acts of terrorism. Based on this reality, it is relevant to the film Sayap-Sayap Patah which can represent a true story about the suicide bombing that occurred at the Polic Building in 2018. This study aims to determine the representation of the ideology of radicalism and controversy in the film Sayap-Sayap Patah. The subject of this research is the Broken Wings Film. The method in this study uses qualitative research methods using Roland Barthes's semiotic analysis approach (connotative meaning, denotation, and myth). The results of the study show that there are several indicators of the ideological depiction of radicalism carried out by Leong. This film shows how Leong formed his group to carry out his mission in carrying out a noble struggle and prioritizing "jihad" with acts of terrorism. The meaning of this film also shows how the ideology of radicalism attacks the ideology of the nation to destroy the morale and unity of the nation in real life. Keywords : Broken Wings Film, Radicalism Ideology, Representation, Roland Barthes Semiotics